Analisis Perbandingan Metode Kuz-Ram dengan Digital Image Analysis Terhadap Ukuran Fragmentasi dalam Desain Peledakan Produksi Batugamping Pada PT. Semen Tonasa - Sakti, Putra (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2021)
Semen Tonasa is a company that operating in cement industry at east Indonesia region with the base material is limestone. PT. Semen Tonasa is located in Pangkajene Islands Regency, South Sulawesi Province. Mining method used is quarry method with blasting as a mine activity to open the materials. In every blasting activity needed the size of fragmentations is not more than 80 cm ≤ 15%. That size is obtained base on the capability of crusher mouth. Analysis method of rocks fragmentation that used was digital image analysis actually on the field with using split-dekstop software and theoretically with Kuz-Ram method. That thing was taken to compare percentage distribution of size fragmentation of blasting activity. The result of fragmentation analysis on mining area at PT. Semen Tonasa, was conducted on two locations of data interpretation that were at B7 and B8. The geometries applied at Quarry B7 was burden of as 5,04 m and a spaced of 6,03 resulting fragmentation size ≥ 80 or 8,15% and at Quarry B8 was a burden of 5,2 m and a spaced of 5,7 m resulting fragmentation size 5,61%, these were based on split-Dekstop method. In other hand that results were contrary with the prediction of Kuz-Ram method by the percentage of fragmentations at Quarry B7 equal to 24,17% and B8 equal to 22,99% with the size of fragmentation ≥ 80 cm.